2018
DOI: 10.1111/php.12976
|View full text |Cite
|
Sign up to set email alerts
|

Is Proflavine Exposure Associated with Disease Progression in Women with Cervical Dysplasia? A Brief Report

Abstract: Proflavine is an acridine dye used with high‐resolution microendoscopy for in vivo diagnostic evaluation of cervical epithelial cells. However, there are concerns that even short‐term exposure of cervical tissue to dilute proflavine may increase cervical cancer risk. We performed a retrospective analysis of women referred for colposcopy to Barretos Cancer Hospital comparing the risk of cervical disease progression in those whose cervical tissue was (n = 232) or was not exposed (n = 160) to proflavine. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…It was observed that there were no noticeable differences in disease progression from the initial diagnostic to invasive cancer between the proflavine exposed and control groups overall. Some risks of cervical dysplasia progression were observed, but these findings were in good correlation with those observed for the natural cases of cervical cancer [35]. These findings are thus promising for using PRO in early diagnostic.…”
Section: Clinical Trials Of Methylene Blue and Proflavinesupporting
confidence: 68%
See 4 more Smart Citations
“…It was observed that there were no noticeable differences in disease progression from the initial diagnostic to invasive cancer between the proflavine exposed and control groups overall. Some risks of cervical dysplasia progression were observed, but these findings were in good correlation with those observed for the natural cases of cervical cancer [35]. These findings are thus promising for using PRO in early diagnostic.…”
Section: Clinical Trials Of Methylene Blue and Proflavinesupporting
confidence: 68%
“…The basis of its antibacterial property is its action as a nucleic acid intercalator. As a result of this important property, PRO is routinely used for umbilical cord care in newborn infants in the United States, with rare episodes of toxicity reported thus far [35].…”
Section: Preoperative and Intraoperative Use In Cardiac Surgerymentioning
confidence: 99%
See 3 more Smart Citations